Revisiting the stem proteome of Eucalyptus grandis and Eucalyptus globulus: Identification of temperature-induced changes - de Santana Costa, Marília Gabriela [UNESP]; Feltrim, Daniela; Mazzafera, Paulo; Balbuena, Tiago Santana [UNESP] (Elsevier, 2020)
Eucalyptus grandis and Eucalyptus globulus are important species for the Brazilian forestry industry. E. grandis plantations are mainly found in tropical regions, yet E. globulus plants are usually cultivated under moderate to low temperature conditions. As temperature seems to be a key factor for the planting of these species, we revisited our previously generated shotgun proteomics dataset to identify the main patterns of proteome regulation induced by thermal stimulus and to pinpoint specific proteins involved in the environmental response. Large-scale analysis has pointed out the different proteomic responses of E. grandis and E. globulus under temperature stimulus, with 296 proteins considered to be differentially regulated in the stems of Eucalyptus spp. grown at different temperatures. A stringent filtering approach was used to identify the most differentially regulated proteins. Through the stringent criteria, 66 proteins were found to be enriched in the plant species. Cultivation of E. globulus plants in low-temperature conditions induced the highest number of differentially regulated proteins. Additionally, metabolic proteins were mostly down-regulated, while stress-related proteins were majorly up-regulated in both species. Finally, the subset of the most differentially regulated proteins comprised new candidates of protein markers of temperature stress.
Keywords: Biomarkers; Label-free proteomics; Plant proteomics; Thermal stress